Factors affecting the likelihood of pregnancy and embryonic loss after transfer of cryopreserved in vitro produced equine embryos. (24th October 2018) - Claes, A.; Cuervo‐Arango, J.; van den Broek, J.; Galli, C.; Colleoni, S.; Lazzari, G.; Deelen, C.; Beitsma, M.; Stout, T. A.
Summary: Background: In vitro embryo production (IVEP) is increasingly popular but data assessing the outcome of transferred embryos are scarce. Objectives: To determine the likelihood of pregnancy and embryonic loss after transfer of frozen‐thawed IVP embryos and identify factors influencing success. Study design: Retrospective clinical study. Methods: Blastocysts (n = 261) were produced from immature oocytes of Warmblood mares (n = 116) by Intracytoplasmic Sperm Injection (ICSI) and in vitro culture, and cryopreserved. Thawed IVP embryos were transferred into recipient mares on day 4, 5 or 6 after ovulation. The influence of donor mare (age, reproductive history), recipient mare (age, reproductive status, management; in‐house vs. outpatient, day post‐ovulation), embryo (interval from ICSI to blastocyst formation) and management factors (season when ovum pickup was performed, year and method of transfer) on likelihood of pregnancy and embryonic loss was examined, and the developmental stage of the IVP embryo at the time of transfer was estimated. Results: The percentage of mares pregnant 7–10, 23 and 37 days after transfer was 56% (147/261), 49% (129/261), and 48% (124/261), respectively. Development of IVP embryos after transfer equated to day 5 or 6 in vivo embryos. With the exception of year of transfer, none of the factors had an impact on the likelihood of pregnancy or embryonic loss. Nevertheless, the likelihood of pregnancy tended to be lower for IVP embryos from infertile mares or when embryos were transferred into recipient mares on day 6 after ovulation rather than on day 4 or 5. Finally, the diameter of the embryonic vesicle 7 days post transfer was lower for pregnancies that were lost compared to those that were maintained. Main limitations: Small sample size in some of the donor and recipient mare categories. Conclusions: Cryopreserved IVP embryos should be transferred into recipient mares on day 4 or 5 after ovulation and a slower rate of post transfer vesicle expansion indicates a higher risk of subsequent embryonic loss The Summary is available in Portuguese ‐ see Supporting Information